Interannual variability of carbon fluxes at the North Atlantic Station ESTOC - Pätsch, J.; Kühn, W.; Radach, G.; Santana Casiano, J. M.; Gonzalez Davila, M.; Neuer, S.; Freudenthal, T.; Llinas, O. (Deep Sea Research Part II: Topical Studies in Oceanography, 2002)
The impact of sea surface temperature and wind stress on primary production, export production, and CO2 air–sea exchange at the ESTOC station (29°N, 15.5°W) north of the Canary Islands is the focus of our investigations. A one-dimensional carbon and nitrogen cycling model was applied for the 10-year period 1987–1996. The simulation results compare well with upper layer observations for 1994–1996. Our simulated deep-water particle fluxes mostly overestimate the originally observed values for 1992–1996. On the other hand, the simulated fluxes underestimate the 230Th corrected particle fluxes (Scholten et al., Deep Sea Res. 48 (2001) 1413). Identifying the original observations as lower and the corrected values as upper estimate for the particle flux the simulation results falls in the range between these estimates. The large simulated interannual variability of carbon fluxes is in apparent contrast to the low interannual variability of the meteorological forcing typical for this subtropical regime. The key to this phenomenon lies in the sensitivity of this ecosystem to nutrient supply: depending on the meteorological situation, in different years the mixed-layer depth can or cannot reach the nitracline.